Assessment of Maternal Satisfaction with the Quality of Antenatal Care Rendered by Midwives at A Tertiay Health Institution in the Southeast Nigeria (International Journal of Preventive Medicine and Health (IJPMH), 2023)
In this era of economic challenges health care consumers’ desire quality of care that comes with value and satisfaction. This cross-sectional descriptive study assessed maternal satisfaction with the quality of antenatal care rendered by midwives at a tertiary health institution in the Southeast Nigeria. Three objectives guided the researchers in achieving the purpose of the study. Sample of 171 respondents was drawn from a population of 301 pregnant women using Taro Yameni formula for sample size calculation. Validated investigators’ structured questionnaire with reliability index of 0.70 was used for data collection. Data generated from the study were analyzed through descriptive statistics using SPSS Version 21 IBM. Findings from the study revealed that the pregnant women attending Antenatal clinic at the state tertiary health institution are satisfied with the quality of physical and psychological care rendered by the midwives in the institution. Outstanding in their satisfaction were evidenced in their contentment with blood pressure monitoring (43.4%), weight monitoring (40.9%), directives on family planning (47.4%), reassurance by midwives (40.9%), and confidentiality of privileged information (42.7%). They saw the spacious nature of the ANC care arena as a satisfier too. Greater number of the women (77.8%) believes that they derived their satisfaction of care from the availability of essential drugs and necessary equipment. Finally in order to improve satisfaction with antenatal care, organizational aspects of antenatal care such as reducing waiting times and increasing accessibility to drugs and equipments need to be improved. The researchers recommended that the hospital management should recruit more midwives to reduce the work load on those working at the ANC unit and also provide comfortable environment for the pregnant women attending the ANC.